A Note on q‐Covering Designs in PG(5, q). Issue 8 (18th February 2016) - Cossidente, Antonio; Pavese, Francesco
Abstract: A construction of q ‐covering designs in PG(5, q ) is given, providing an improvement on the upper bound of the q ‐covering number C q ( 6, 3, 2 ) .